We need to find the solution to the equation
![3y^(2)-7y=0](https://img.qammunity.org/2023/formulas/mathematics/college/ib0yhpee9zgertlhhih8l5jin1wheq4fh2.png)
Step 1
Rewrite the expression on the left side, grouping the common factor, as follows:
![\begin{gathered} 3y\cdot y-7y=0 \\ \\ y(3y-7)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f9f6c0asaajx713hvrw5oa0tu0m6cflcel.png)
Step 2
Notice that the above equation holds when one of the factors is zero:
![\begin{gathered} y=0 \\ or \\ 3y-7=0 \\ 3y=7 \\ y=(7)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1fv8h4zvw9b4e46dbja3y1yxmyr2yygrts.png)
Answer
Since both 0 and 7/3 are already reduced to the lowest terms, the answer is
![\begin{gathered} y=0 \\ or \\ y=(7)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1qz7m381zc5zl1egqe0k50hzkma1fcuo6x.png)